Empirical analysis of the effect of the establishment of pilot free trade zone on regional innovation development - Liu, Xinhong; Basah, Norliza Hamir (Asian Economic and Financial Review, 2025)
In order to positively meet new international trade rules, China has put forward the strategy to implement Pilot Free Trade Zones (PFTZs). The extensive establishment of PFTZs has offered a good innovation environment for regional economic development. Consequently, based on data from 30 provinces from 2007 to 2022 as research samples, this study discusses the impact of establishing PFTZs on regional innovation development and examines the policy effect heterogeneities. In addition, digital finance (DF) and the digital economy (DE) are introduced as mediating variables to verify whether DF and DE play a mediating role between building PFTZs and regional innovation. Empirical results show that building PFTZs is beneficial for boosting the regional innovation level. The heterogeneity analysis indicates that the effect of PFTZs policies on the regional innovation level is more pronounced in provinces and cities with higher economic development levels, coastal provinces and cities, and provinces with larger population scales. Furthermore, according to the mediating effect test, it can be found that PFTZs will enhance the regional innovation level through DF and DE. Therefore, it is suggested to continuously promote the strategy of building PFTZs, pay full attention to the deep integration of DF, DE, and regional innovation, and generally improve the regional innovation level.